Prey [videorecording (Blu-Ray)] - Aison, Patrick; Trachtenberg, Dan; Midthunder, Amber; Thrush, Michelle; Mathias, Stefany (20th Century Studios, 2023)
The epic Predator legacy continues with this action-thriller set in the Comanche Nation. When Naru, a fierce and highly skilled young warrior, sets out to protect her people, the prey she stalks turns out to be a highly evolved alien predator leading to a vicious and terrifying showdown.